Penentuan koefisien perpindahan panas permukaan bola berdasarkan pendekatan analitik perpindahan panas tak tunak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
The standard method to determine the coefficient of surface heat transfer on spheres is based on the lumped capacitance method using spherical particles with Biot number less than 0,1. However, most agricultural products with spherical shapes have Blot number greater than 0,1. Several analytical approaches are available to determine the temperature distribution within the spheres with higher Biot number. Accordingly, the objectives of this research were to determine the coefficient of surface heat transfer based on analytical approaches and to compare the values to that determined by the standard method. Samples were spheres made from wood for analytical approach and made from copper for lumped capacitance method. The results indicate that the values of the coefficient of surface heat transfer determined by both methods were significantly similar. The conductivity, and the coefficient of surface heat transfer of spherical wood simultaneously can be determined using the analytical approaches for transient heat transfer on spheres.